1988
DOI: 10.1159/000138420
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sennosides and Related Compounds on Intestinal Transit in the Rat

Abstract: The effect of pure sennosides A + B on large intestinal transit (LIT) was investigated in the rat. LIT was defined as the time from intracecal administration of a color marker through a chronically implanted catheter until first appearance of colored feces. Sennosides (50 mg/kg, administered orally 2–24 h before the marker) reduced LIT from > 6 h in controls to a minimum of 30–20 min after a 4- or 6-hour pretreatment. Longer pretreatment times increased LIT again reaching normal values after 24 h. Intracecal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…Most prominent are the X-ray (3) and scintigraphic techniques (4), which have been used to monitor orally ingested capsules containing radioopaque material or gamma-emitters. On the other hand, noninvasive techniques such as ultrasound (5), metal detectors (6), magnetic field detectors (7), and dyes (8) have been used to avoid the adverse effects of ionizing radiation. However, all these methods have been severely restricted due to intrinsic constraints such as low temporal or spatial resolution, lack of complementary anatomical information, or incomplete spatial information.…”
mentioning
confidence: 99%
“…Most prominent are the X-ray (3) and scintigraphic techniques (4), which have been used to monitor orally ingested capsules containing radioopaque material or gamma-emitters. On the other hand, noninvasive techniques such as ultrasound (5), metal detectors (6), magnetic field detectors (7), and dyes (8) have been used to avoid the adverse effects of ionizing radiation. However, all these methods have been severely restricted due to intrinsic constraints such as low temporal or spatial resolution, lack of complementary anatomical information, or incomplete spatial information.…”
mentioning
confidence: 99%
“…Donowitz et al [5] showed that the changes in active electrolyte transport with senna were dependent on Ca2+ in the serosal but not the mucosal bathing solution in vitro. Leng-Peschlow [6] showed that calcium chan nel blockers only prolonged large intestinal transit time reduced by sennosides and did not suppress the appearance of soft faeces. The calcium ion is widely accepted as a funda mental regulator in intracellular processes in most cell types.…”
mentioning
confidence: 99%
“…Twenty-four hours after a high dose of sennosides (50 mg/kg) inducing a pro nounced diarrhea, transit rate and fecal con sistency were completely normalized [2], The aim of the present study was to follow the time-course of secretion over a full 24-hour period after the same high dose of sennosides to ascertain which importance secretion plays for the laxative effect.…”
Section: Introductionmentioning
confidence: 94%